Frontispiece: Oligonucleotides with Cationic Backbone and Their Hybridization with DNA: Interplay of Base Pairing and Electrostatic Attraction. Issue 7 (1st February 2018) - Schmidtgall, Boris; Kuepper, Arne; Meng, Melissa; Grossmann, Tom N.; Ducho, Christian
Abstract : The artificial nucleosyl amino acid (NAA) internucleoside linkage was used to construct cationic oligonucleotide analogues. Corresponding oligomers hybridized to native DNA with high affinity. Using melting temperature experiments and CD spectroscopy, it was shown that Watson–Crick base pairing was crucial for this duplex formation, but unspecific electrostatic binding also contributed. These results indicate that the number of positive charges in oligonucleotide analogues for biomedical applications should be limited. For more information, see the Full Paper by T. N. Grossman, C. Ducho, et al. onpage 1544 ff.